Uncontrolled organ donation after out-of-hospital cardiac arrest. Literature review - M. G. Minina; P. A. Drozdov; V. M. Sevostyanov; E. A. Tenchurina; A. A. Nevredimov; P. A. Davydov; O. V. Shatskova (Вестник трансплантологии и искусственных органов)
Organ transplantation is the best therapy for terminal and irreversible organ failure. The global development of organ transplantation as a type of medical care is inextricably linked to the establishment of neurological criteria for declaring human death (brain death). In the early evolutionary period of transplantation, organs were used, mainly kidneys, obtained from donors whose death was ascertained in accordance with the generally accepted criteria of cessation of blood circulation and respiration. As this type of organ donation developed, numerous terms were used in the world literature to designate it, such as ‘asystolic donors’, ‘non-heart beating donors’, ‘donors after cardiac death’, etc. In Russia, there is an established practice of dealing with donors after cardiac death (DCD), but the active development of Russian transplantology in the last 20 years is primarily associated with brain-dead organ donation. However, countries with the most active and advanced organ donation practices have in recent years been successfully dealing with donors who have suffered sudden out-of-hospital cardiac arrest (OHCA). Previously, this type of donation was considered inaccessible due to the unacceptable warm ischemia time and consequently severe damage to donor organs. Due to the development of new technologies in emergency medical care, it became possible to transport a patient with clinical death that occurred in an outof-hospital setting, to the hospital, while providing cardiopulmonary resuscitation by means of automatic chest compression and artificial ventilation. The article presents historical aspects of donation after cardiac death, and the most actualized definitions and practices of dealing with such donors.